Digital Art Photography for Dummies - Bamberg, Matthew (Wiley Publishing, 2011)
So you’ve made the jump to digital photography and you’re having a ball with your new camera, right? Now, you’re wondering just what it would take to make your photos a little more than just snapshots. Well, Digital Art Photography For Dummies is a great place to find out!